SEDIMENTARY CHARACTERISTICS OF SAND DUNES IN CAU NGANG AND TRA CU DISTRICTS, TRA VINH PROVINCE AND THEIR FRESHWATER - BEARING CAPACITY - Lap, Nguyen Van; Kim Oanh, Ta Thi (Vietnam Journal of Earth Sciences, 2014)
Sedimentary characteristics of sand dunes and related deposits in Cau Ngang and Tra Cu Districts, Tra Vinh province are clarified to confirm freshwater-bearing capacity. In the study area, 05 OSL ages of sand dunes are dated from 1620 ± 90 years before present (BP); 1590 ± 90; 1100 ± 60; 970 ± 50 and 770 ± 40 showing the sand dune system of this area had been evolved in progradation of Mekong river delta in late Holocene. Distribution features of aquifer in sand dune in Cau Ngang and Tra Cu are identified on the base of sedimentary structures of sand dunes and surrounding deposits. Aquifer in sand dune with lenticular forms is recharged naturally by rainy water so the water volumn is changed upon the season. The change of water level is appoximately of 1.8 -2.6 during dry and wet seasons. Freshwater-bearing in sand dune is Bicarbonate-clorur-natrium. In the wet season, rainy water is natural recharge source; in the dry season, fresh water from canal or small river would be good artificial recharge source to increase groundwater reserves. References Fontaine, H., 1970. Trace d’ un ancien rivage marin a Cai lay (du Vietnam). Archives Geologique, Saigon Vietnam 13, 147-154. Nguyen Van Lap, Ta Thi Kim Oanh, Tateishi, M., 2000. Late Holocene depositional environments and coastal evolution of the Mekong River Delta, Southern Vietnam. Journal of Asian Earth Science 18, 427-439. Tạ Thị Kim Oanh, Nguyễn Văn Lập, 2006. Tướng trầm tích Holocen tương ứng với dao động mực nước biển vùng Vĩnh Long - Trà Vinh, Đồng Bằng Sông Cửu Long, Tạp chí Các Khoa học về Trái Đất, T.28, 3, 329-335. Tạ Thị Kim Oanh, Nguyễn Văn Lập, Huỳnh Thị Thanh Tâm, Nguyễn Thị Mộng Lan, Phạm Công Luyện, 2012. Trầm tích giồng cát huyện Duyên Hải tỉnh Trà Vinh và tiến hóa Holocen châu thổ sông Cửu Long, Tạp chí Các Khoa học về Trái Đất, T.34, 3ĐB, 335-340. Sở Tài nguyên và Môi trường tỉnh Trà Vinh, 2010. Bản đồ hiện trạng sử dụng đất tỉnh Trà Vinh năm 2010 tỷ lệ 1/25.000.